Impacts on water transport networks after three widespread volcanic ashfalls in Andean Patagonian lakes - Pablo Salgado; Gustavo Villarosa; Débora Beigt; Valeria Outes; Carol Stewart; Fernando Baranzini (Volcanica, 2023)
Although the impacts of volcanic ashfall on air transport and land transport networks are well documented, little information exists about volcanic ash effects on water transport. Three recent widespread ashfall events severely affected the extensive shipping activity that takes place in the many lakes of Andean Patagonia, Argentina. By means of impact assessment fieldtrips, meetings, semi-structured interviews, and expert consultation, we surveyed and categorized impacts of volcanic ash on ships, ports and shipping activities, also assessing most effective mitigation strategies undertaken, including clean-up actions. To better catalogue type and severity of impacts, we expand on available damage scales developed for critical infrastructure, to include more specific details about water transport systems. Our contribution ultimately aims to communicate to emergency managers, and the volcanological and nautical communities, the most likely outcomes from explosive volcanic eruptions on shipping, along with best-practice advice for mitigating adverse effects.